Pengaruh Return On Asset (ROA), Debt to Equity Ratio (DER), Dan Inventory Turnover (ITO) Terhadap Harga Saham (Studi Empiris Pada Perusahaan Sektor Consumer Goods Industry Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Fahma Lintang Nabila; Ronny Malavia Mardani; Muhammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe consumer goods industry is one of the companies listed on the IDX and its shares are actively traded. The purpose of this study was: 1) to find out the effect of Return on Assets (ROA) on stock prices in consumer goods industry companies; 2) to find out the effect of Debt to Equity Ratio (DER) on stock prices in consumer goods industry companies; and 3) to find out the effect of Inventory Turnover (ITO) on stock prices in consumer goods industry companies. By using a sample of consumer goods industry companies listed on the Indonesia Stock Exchange and the study period in 2016-2018. The data analysis techniques used in this study include multiple linear regression analysis, normality test, classic assumption test and hypothesis test. The results showed that Return On Assets (ROA) had a positive effect on stock prices, Debt to Equity Ratio (DER) negatively on stock prices and Inventory Turnover (ITO) on stock prices. Keywords: Return On Assets (ROA), Debt to Equity Ratio (DER), Inventory Turnover (ITO), Stock Prices.